2016
DOI: 10.1159/000450837
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Impairment in Advanced Chronic Kidney Disease: The Canadian Frailty Observation and Interventions Trial

Abstract: Background: Chronic kidney disease (CKD) affects more than one third of older adults, and is a strong risk factor for vascular disease and cognitive impairment. Cognitive impairment can have detrimental effects on the quality of life through decreased treatment adherence and poor nutrition and results in increased costs of care and early mortality. Though widely studied in hemodialysis populations, little is known about cognitive impairment in patients with pre-dialysis CKD. Methods: Multicenter, cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
42
0
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 53 publications
4
42
0
7
Order By: Relevance
“…Cognitive impairment, as measured by the MoCA, was highly prevalent in our pretransplant evaluation population which consisted mainly of Hispanics and Native Americans. This finding is consistent with previous studies showing that cognitive impairment is prevalent in the dialysis population and also confirmed the study by Sequist et al that Native Americans are less likely to be placed on the wait‐list compared with Whites. We found that advanced age, low education level and being on dialysis at the time of evaluation were associated with cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%
“…Cognitive impairment, as measured by the MoCA, was highly prevalent in our pretransplant evaluation population which consisted mainly of Hispanics and Native Americans. This finding is consistent with previous studies showing that cognitive impairment is prevalent in the dialysis population and also confirmed the study by Sequist et al that Native Americans are less likely to be placed on the wait‐list compared with Whites. We found that advanced age, low education level and being on dialysis at the time of evaluation were associated with cognitive impairment.…”
Section: Discussionsupporting
confidence: 93%
“…Cognitive impairments are frequently observed among individuals undergoing haemodialysis (HD) (Griva et al ; Lux et al ; Song et al ; Zammit et al ; Foster et al ; O’lone et al ; Drew et al . ; Iyasere et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Cognitive impairments are frequently observed among individuals undergoing haemodialysis (HD) (Griva et al 2010;Lux et al 2010;Song et al 2011;Zammit et al 2015;Foster et al 2016;O'lone et al 2016;Drew et al 2017;Iyasere et al 2017). Such deficits may take the form of memory and attention impairment, reduced psychomotor speed and accuracy, and reduced mental efficiency (O'lone et al 2016;Drew et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For example, 55% of the dialysis population has some form of diabetes, which in turn is associated with peripheral neuropathy, carpal tunnel syndrome, arthritis, and macular degeneration. Additionally, given that the overall mean age at dialysis initiation is approximately 64 years old, rates of cognitive impairment are estimated to affect a significant proportion of dialysis patients; cognitive impairment affects a person's judgment and dexterity, hindering their ability to self‐manage complicated HHD systems. Moreover, although self‐care can promote self‐empowerment, an individual's support network often needs to be involved in a patient's care; and indeed this is reflected in several studies that suggest home dialysis users tend to be younger and married or cohabitating, with fewer comorbidities …”
Section: Discussionmentioning
confidence: 99%